2009
DOI: 10.1002/ajpa.21122
|View full text |Cite
|
Sign up to set email alerts
|

Shallow‐water habitats as sources of fallback foods for hominins

Abstract: Underground storage organs (USOs) have been proposed as critical fallback foods for early hominins in savanna, but there has been little discussion as to which habitats would have been important sources of USOs. USOs consumed by hominins could have included both underwater and underground storage organs, i.e., from both aquatic and terrestrial habitats. Shallow aquatic habitats tend to offer high plant growth rates, high USO densities, and relatively continuous USO availability throughout the year. Baboons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
87
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 101 publications
(119 reference statements)
5
87
1
1
Order By: Relevance
“…Several studies have suggested that exploitation of energy-rich geophytes or underground storage organs (USOs) (bulbs, corms, tubers, and rhizomes) represented an important adaptive shift in hominin evolution, especially as related to the transition to early Homo (e.g., [39][40][41]. In general, most USOs are C 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that exploitation of energy-rich geophytes or underground storage organs (USOs) (bulbs, corms, tubers, and rhizomes) represented an important adaptive shift in hominin evolution, especially as related to the transition to early Homo (e.g., [39][40][41]. In general, most USOs are C 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining (C 3 ) portion of A. bahrelghazali's diet may have included C 3 macrophytes, as suggested in ref. 41, or the more "traditional" hominoid foods such as fruits, pods, flowers, and insects. The semiarid terrestrial flora that today stretches away from the current Lake Chad and colonizes the dunes includes Hyphaene thebaica (doum palm), Acacia nilotica, and Ficus ingens (42), all of which produce widely consumed fruits and pods (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…These similarities in physical attributes suggest behavioral differences were what allowed for overlapping ranges and local coexistence (sympatry) of both hominins. For instance, differences in seasonal subsistence strategies or different behavior during periods of drought and limited food could have reduced local hominin competition and fostered diversification via niche specialization (27)(28)(29). Physical and isotopic properties of fossil teeth indicate P. boisei was more water-dependent [low enamel δ…”
mentioning
confidence: 99%
“…Although 13 C-enriched enamel is commonly attributed to consumption of C 4 grasses or meat from grazers (14), this was not likely, because P. boisei craniodental features are inconsistent with contemporary gramnivores (24,25) or extensive uncooked flesh mastication (26). Numerous scholars have proposed the nutritious underground storage organs (USOs) of C 4 sedges were a staple of hominin diets (14,24,26,27). Consistent with this suggestion, occurrences of n R 23 attest to the presence of sedges at FLK NN and FLK N (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation